Development of land transport connections between Asia and Europe and their possible impact on vector introductions into European Countries - Aleksandra Gliniewicz (National Institute of Public Health - National Institute of Hygiene, 2019)
The possibility of transfer of several organisms - disease vectors by land transportation Asia - Europe corridors into European countries is discussed. In Europe most alien species are of Asiatic origin. Trade and exchange of goods have developed very intensively for the beginning of the XXI century between Asia and European Union countries both by sea and land routes. Road and railway connections shorten the time of goods' transport from China to Europe to 10,5 - 12 days. Shorter travel time and increased intensity of trade can increase the risk of introducing vector organisms from Asian countries to Europe. Existing legal international regulations (International Health Regulations, IHR) provide procedures to protect goods and persons against the carriage of organisms - vectors at every stage of transport and travel. Mass passenger and car traffic at border crossing points increase the likelihood of vector organisms entering as random stowaways; therefore it is proposed to intensify educational activities to make people aware of the danger posed by the transport of alien species of arthropods and what preventive actions to take. Unloading goods in a transit country (such as Poland) may take place at a transshipment center located near the border or inland. It is postulated to introduce a 400 m vector monitoring zone around both.